ANALISIS STABILITAS DAN ALTERNATIF PERKUATAN LERENG PROYEK REHABILITASI BENDUNGAN PACAL KABUPATEN BOJONEGORO - Lutfiah, Ine; Solin, Dian Purnamawati; Farichah, Himatul (Universitas Muhammadiyah Surabaya, 2023)
Pacal Dam is infrastructure used for irrigation purposes for the Bojonegoro community. However, in 2014 there was heavy rain and it triggered a landslide on the right side of the support cliffspillway. Therefore, this research was carried out to determine the condition of the slopes of the Pacal Dam project in existing conditions and to find out safe alternatives for handling it as planned. With assistive programsPlaxis can find out the safety value of the slope in its existing condition and when handling is carried out. The safety value when existing conditions have a less safe value, namely 1.1061 or less than 1.50. Therefore, handling is carried out by adjusting the slope of the slope (cut and fill) and strengthening by usingSoil Nailing. Safety value when excavating and filling (cut and fill) of 2.1179 which means it is safe. And for security value with reinforcementSoil Nailing The security value is 2.9407, with long planningnail 10 meters, vertical horizontal distance 1 meter, and with a slope of 15. From the slope results, both treatments met the planned standard safety value of 1.5. Therefore, slope strengthening can be used as an alternative for handling slope stability.